Investigation characteristics of partial discharges in artificial defects of power transmission lines - D. A. Polyakov; N. A. Tereschenko; I. V. Komarov; K. I. Nikitin; U. V. Polyakova (Омский научный вестник)
The article describes the study of the characteristics of partial discharges (PD) in various types of artificial defects in cable lines. A total of 13 types of insulation defects are considered. The PD measurements are carried out using a high AC voltage source and a commercial PD recorder. For each type of defect, diagrams of the amplitude-phase distribution of PD (APDPD), the average value of the apparent discharge, and the PD intensity are obtained. The results of the study show that most of the defects of insulators of overhead power lines have a relatively high intensity of partial discharges with a small average apparent charge. In the samples of cable lines, relatively high values of intensity and average apparent discharge are recorded in the presence of a defect in the end seal and a defect in the ground electrode in the form of a needle. The results obtained can be used in the development of devices for detecting defects, as well as for expanding the base of diagrams (APDPD).